Degradation and Transmission of Tau by Autophagic-Endolysosomal Networks and Potential Therapeutic Targets for Tauopathy - Jiang, Shanya; Bhaskar, Kiran (Frontiers in Molecular Neuroscience, 2020)
Tauopathies are a class of neurodegenerative diseases, including Alzheimer’s disease (AD), Frontotemporal Dementia (FTD), Progressive Supranuclear Palsy (PSP), Corticobasal Degeneration (CBD), and many others where microtubule-associated protein tau (MAPT or tau) is hyperphosphorylated and aggregated to form insoluble paired helical filaments (PHFs) and ultimately neurofibrillary tangles (NFTs). Autophagic-endolysosomal networks (AELN) play important roles in tau clearance. Excessive soluble neurotoxic forms of tau and tau hyperphosphorylated at specific sites are cleared through the ubiquitin-proteasome system (UPS), Chaperon-mediated Autophagy (CMA), and endosomal microautophagy (e-MI). On the other hand, intra-neuronal insoluble tau aggregates are often degraded within lysosomes by macroautophagy. AELN defects have been observed in AD, FTD, CBD, and PSP, and lysosomal dysfunction was shown to promote the cleavage and neurotoxicity of tau. Moreover, several AD risk genes (e.g., PICALM, GRN, and BIN1) have been associated with dysregulation of AELN in the late-onset sporadic AD. Conversely, tau dissociation from microtubules interferes with retrograde transport of autophagosomes to lysosomes, and that tau fragments can also lead to lysosomal dysfunction. Recent studies suggest that tau is not merely an intra-neuronal protein, but it can be released to brain parenchyma via extracellular vesicles, like exosomes and ectosomes, and thus spread between neurons. Extracellular tau can also be taken up by microglial cells and astrocytes, either being degraded through AELN or propagated via exosomes. This article reviews the complex roles of AELN in the degradation and transmission of tau, potential diagnostic/therapeutic targets and strategies based on AELN-mediated tau clearance and propagation, and the current state of drug development targeting AELN and tau against tauopathies.